Financial Literacy and Financial Self-Efficacy as Determinants of Responsible Financial Behavior: The Effect of Fintech Adoption and Financial Stress - Febriana Louw; Giriati Giriati; Helma Malini (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
This study is motivated by the increasing complexity of financial behavior in the digital era, where the rapid expansion of Financial Technology (Fintech) has enhanced access to financial services but has not necessarily led to more responsible financial behavior. Although financial literacy and financial self-efficacy are recognized as key determinants of financial decision-making, empirical findings remain inconsistent, indicating the need to explore additional mechanisms such as fintech adoption. This study aims to examine the effects of financial literacy and financial self-efficacy on responsible financial behavior, incorporating fintech adoption as a mediating variable and financial stress as a moderating variable. A quantitative survey design was employed, involving 236 Generation Z respondents in Pontianak, Indonesia, and analyzed using SEM-PLS. The results reveal that financial literacy has a positive but insignificant direct effect, while financial self-efficacy significantly influences responsible financial behavior. Fintech adoption is found to have a positive effect and mediates both relationships. Additionally, financial stress weakens the relationship between financial literacy and financial behavior. In conclusion, promoting responsible financial behavior requires the integration of financial knowledge, self-efficacy, and effective utilization of fintech.